LAYANAN BIMBINGAN KELOMPOK TENTANG TATA KRAMA PESERTA DIDIK KELAS IX SMP MUJAHIDIN PONTIANAK - Santri Tri Wansih; Muhammad Asrori; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
Abstract Group guidance services are a way of providing assistance (guidance) to individuals (students) through group activities. One of the most expected in the implementation of group guidance on etiquette is to improve students' behavior and prevent them from unverified acts. The research problem is "How is the guidance service group about the manners of students of class IX SMP Mujahidin Pontianak?". Purpose of study to get description about group guidance service about the manners of students of class IX SMP Mujahidin Pontianak. The method used is descriptive with quantitative approach in the form of survey study. Research Population of 23 students. Data collection techniques used are indirect communication with data collection tools in the form of questionnaires. Data analysis technique is percentage. Overall the implementation of group guidance on manners reached 85% with good category, which means already implement the steps of group guidance in accordance with the theory. At the stage of forming the implementation of group guidance on etiquette achieve results 86.47% with good category. At the transition stage the implementation of group guidance on etiquette achieved 92% results with good category. At the core activity stage, group guidance on manners reaches 84% result with good category. At the termination stage, the group guidance on manners reaches 80% with good category. Keywords: Group Guidance Services, Etiquette